PERSEPSI GURU DAN TEMAN SEBAYA TERHADAP SISWA CERDAS ISTIMEWA BERBAKAT ISTIMEWA - Dia Pitaloka; Liza Murniviyanti; Melinda Puspita Sari Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the perceptions of teachers dan peers toward Gifted and Talented Students (CIBI) at SD Baptis Palembang. CIBI students are individuals with exceptional potential in both academic and non-acamedic areas who require specil support within the school environment. This research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. Informants consist of teachers, peers, CIBI students, and the principal. The findings reveal that teachers generally have positive perceptions of CIBI students, demonstrated through differentiated teaching strategies, academic challenges, and strong social-emotional support. Peers show good acceptance and maintain healthy social interactions, although some issues such as jealousy or stereotyping occasionally arise. Influencing factors include teachers' educational backgrounds, school culture, and students' social experiences. CIBI students’ involvement in academic and extracurricular activities contributes positively to their cognitive, social, and emotional development. This study recommends strengthening teacher training on the characteristics of gifted students and developing inclusive and supportive school policies for CIBI learners.